(untitled) (Experimental biology, 2015)
The article studied the characteristics of the anatomical structure and biometrics stems some dominant plant communities of middle Trans-Ili Alatau, species such as Potentilla asiatica Juz., Potentilla canescens Bess., Galium aparine L., Artemisia dracunculus L., Galatella fastigiiformis Novopokr. The features of the anatomical structure and the biometrics stems of plants Potentilla asiatica Juz., Potentilla canescens Bess., Galium aparine L., Artemisia dracunculus L., Galatella fastigiiformis Novopokr. depending on the location of their growth.